Analysis of Shooting Ability in Soccer Games of Class V Students of SDI Bontoala, Gowa Regency - Ricardo Valentino Latuheru (Journal Physical Health Recreation (JPHR), 2025)
Shooting ability in football is one of the essential motor skills to be developed since elementary school age, because it is closely related to the game performance and psychomotor development of students. This study aims to analyze the level of shooting ability of grade V students of SDI Bontoala and identify their performance classification based on standardized measurement scores. The method used is a quantitative descriptive approach, with data collection techniques in the form of shooting skill tests given to 17 male students from a total population of 70 students. The data obtained were analyzed using descriptive statistics including average scores, frequency distributions, and classification of ability categories. The results showed that most students (35.3%) were in the "Low" category, while only one student (5.9%) was included in the "Very High" category. The average score of students' shooting ability was 35.5 points, indicating the need for a more effective, structured, and tailored shooting technique learning strategy to the characteristics of individual students. These findings provide an important contribution to the development of Physical Education, Sports, and Health (PJOK) learning at the elementary school level, especially in the aspects of evaluating and coaching basic football technique skills.